The Using of Jigsaw Technique in Writing Narrative Text (Study Case First Semester of STIKOM Tunas Bangsa Pematangsiantar) - Ika Purnama Sari; Purba, Anita; Nasution, Asmarani; Roslaini; Khairunnisa Sormin, Rizky; Setiawati; Anggraini, Yanti (Universitas Sarjanawiyata Tamansiswa, 2024)
The jigsaw is the technique that can be used in many different ways to increase the involvement of students in their own learning. Jigsaw technique can create an effective learning environment. By the jigsaw technique, the students are divided into groups. The groups consist of 5-6 students. The purpose of this research is to study the effect of jigsaw technique on the academic performance of the students in writing narrative. The research has been performed on first semester students of STIKOM Tunas Bangsa Pematang Siantar. The researcher wanted to find out whether or not Jigsaw Technique can increase the students writing skill and to analyze the classroom situation when the Jigsaw Technique is implemented in writing class. This research used CAR and composed for two or more cycles then it observed and evaluated to identify all facts including the success and the failure of the action. After the implementation of jigsaw Technique in every cycle, the students’ writing scores were getting better. It can be seen from the result of students’ average score Cycle 1 was 46.86 and Cycle 2 was 82.23. It can be concluded that Jigsaw Technique can increase their ability in writing narrative text.